Change in Free To Total Prostate Specific Antigen Ratio Following Transurethral Resection of Prostate in Patient With Benign Prostatic Hyperplasia - Ali, SM Yunus; Islam, Md Saiful; Amin, Mohammad Al; Choudhury, Md Golam Mowla; shamim, Isteaq Ahmed (Bangladesh Journal of Urology, 2020)
Objective- To determine the changes in free to total serum prostate specific antigen (PSA) ratio level after transurethral resection of prostate (TURP) in BPH patients at different interval of time. Materials & Methods- A total of 93 patients undergoing TURP for benign enlargement of prostate were included in the study. Serum total PSA and free PSA were assessed before operation and on the Ist and 7th postoperative day and at month 3 to determine the changes in total PSA, free PSA and free to total PSA ratio following TURP. Result- The preoperative mean total PSA, free PSA and free to total PSA ratio were 3.5 :L 1.7 ng/ml, 0.781 0.21 ng/ml and 0.28 + 0.07. In terms of IPSS, 75(80.7%) patients had severe lower urinary tract obstruction and 18(19.3%) moderate obstruction. Histopathological examination of the resected prostatic tissue revealed that all the 93 patients had benign prostatic lesion. Conclusion-The free and total PSA in first few days increases and thereafter it decreases in 3 months period following transurethral resection of prostate in men with BPH. As both these parameters decrease proportionately, the free to total PSA ratio remains consistent. If free to total PSA ratio decreases it raises suspicision about the early changes in malignancy. Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.83-87